"It changes the way I participate": women wrestlers` menstrual cycle experiences - McPherson, T.; Adam, M. E. K.; Davenport, M. H.; McHugh, T.-L. F. (Psychology of Sport and Exercise, 2026)
Consistent with general trends in research from around the world, Western ideologies and methodological approaches dominate sport research focused on women athletes' experiences with their menstrual cycles. The purpose of this community-based participatory research (CBPR) study was to employ an Etuaptmumk/two-eyed seeing (E/TES) approach to explore women wrestlers' experiences with their menstrual cycles in training and competition. Purposeful sampling was used to recruit seven young women wrestlers between 16 and 20 years old. Centred in Indigenous methodology, data were generated via talking circles facilitated by two Indigenous Elders, along with follow-up one-on-one semi-structured interviews. Consistent with a CBPR approach, data were analyzed using a three-phase process of content analysis that included the preparation, organization, and reporting of data. Findings are represented by five main themes, highlighting how young women wrestlers' complex menstrual cycle experiences are shaped by feelings of inconvenience and fears of unexpectedly bleeding through clothing. Such experiences are compounded by participating in a sport environment that promotes a culture of no excuses and where coaches, particularly men coaches, may lack the necessary knowledge to support athletes' as they navigate their menstrual cycle in sport. Finally, participants highlighted how teammate support from other woman wrestlers, as well as a change in narrative that focuses on the power of women's menstrual cycles, are essential for supporting young women wrestlers navigate menstrual cycle experiences. This study serves as an example of how Indigenous perspectives and methodologies in sport research foster in-depth understandings of athletes' menstrual cycle experiences.